A review: current issues on plant tissue culture of rice / Ummi ‘Athirah Mohamad Lutfi - Mohamad Lutfi, Ummi ‘Athirah (Faculty of Plantation and Agrotechnology, 2016)
External and internal factors that affect callus induction and regeneration of rice plant on tissue culture medium had been studied. Factors such as genotypes, carbon source, explant selection, hormone and gelling agent were found gave an effect to both callus induction and regeneration in rice. Among all the factors, genotypes and medium concentration were consider as the major factor. Based on the previous studied found that different types of rice genotypes showed different response toward tissue culture media. Besides, there were a lot of media used in tissue culture such as MS, LS, N6, etc. MS media is the most and common media used in tissue culture of rice. Auxin and cytokinin are the most important hormone used in tissue culture. The optimum medium was well response in callus induction for almost rice genotypes is MS + 2mg/l 2, 4- D. While the optimum hormone used in regeneration of rice is 2mg/l BAP + 0.5mg/l NAA + 0.5mg/l Kin. Another factor that considered in tissue culture technique is gelling agent. Agar, agarose, phytagel or gelrite are example of gelling agents in tissue culture. Agar is the most common gelling agent used in tissue culture. The right amount of nutrient in tissue culture media is important in order to produce high amount and quality of callus and plant regeneration.